2015
DOI: 10.1002/ppsc.201500136
|View full text |Cite
|
Sign up to set email alerts
|

Controllable and Predictable Viscoelastic Behavior of 3D Boron‐Doped Multiwalled Carbon Nanotube Sponges

Abstract: 3D carbon nanotube (CNT)-based macrostructures are the subject of extensive attention because the outstanding properties of 1D and 2D nanostructures have not been fully translated into key engineering applications. Generation of 3D CNT architectures with covalent junctions could endow the new materials with extraordinary mechanical properties. In this study, detailed experimental characterization and statistical comparison are carried out on 3D boron-doped multiwalled CNT (CB x MWNT) sponges with covalent junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…This result also validates our initial hypothesis that a stretch along the CNT axis rarely happens in a compressed sponge due to its incomparable stiffness compared to that of junctions. Moreover, the simulation output gives an insight into our previous observation that the 3-D CNT sponge with covalent junctions shows a comparatively smaller modulus than its pristine counterpart, undoped-MWCNT sponges [8], while the presence of elbow-like junctions endows the sponge with controllable and remarkable mechanical flexibility. Considering that the junction stiffness could be regulated by the dopant For both CBxMWCNT and N-MWCNT sponges, the predicted junction stiffness varies with the sponge density.…”
Section: Properties Of Covalently Bonded Cnt Junctionsmentioning
confidence: 97%
See 4 more Smart Citations
“…This result also validates our initial hypothesis that a stretch along the CNT axis rarely happens in a compressed sponge due to its incomparable stiffness compared to that of junctions. Moreover, the simulation output gives an insight into our previous observation that the 3-D CNT sponge with covalent junctions shows a comparatively smaller modulus than its pristine counterpart, undoped-MWCNT sponges [8], while the presence of elbow-like junctions endows the sponge with controllable and remarkable mechanical flexibility. Considering that the junction stiffness could be regulated by the dopant For both CBxMWCNT and N-MWCNT sponges, the predicted junction stiffness varies with the sponge density.…”
Section: Properties Of Covalently Bonded Cnt Junctionsmentioning
confidence: 97%
“…Moreover, we found that the MWCNT sponges with covalent junctions have drastically different mechanical behaviors with the pristine (undoped) sponges, including the plastic, elastic, viscoelastic, and dynamic properties. CBxMWCNT sponge is demonstrated as a more predictable and stable material than the undoped-MWCNT sponge [8]. This difference implies that covalent junctions may play a critical role in shaping the mechanical behaviors of 3D CNT sponges.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations